A new way back for social democracy?: The EU referendum and its lessons for the left. Issue 1 (June 2016) - Bogdanor, Vernon
Abstract : Vernon Bogdanor outlines the opportunities for the left in the wake of the Brexit vote, to renew its relationship with working‐class voters, to refocus policy and resources on undersupported areas, and to pursue electoral reform to help start to close the divisions that the referendum has exposed.